POP-16 Evaluación quimiotaxonómica preliminar de tres especies vegetales del género Piper (Piperaceae) mediante el uso de técnicas HPTLC y CPC - Quintero Correa, Miguel; Modesti Costa, Geison (Revista Productos Naturales, 2022)
Piper is a genus of plant species that belongs to piperaceae family which is distributed around the globe specifically around tropical regions. These plants are of great importance from the ecological and economical stance, especially Piper nigrum, pepper, which is used worldwide as a spice.